Effect Of Training Level On Environmental Awareness Among Northern Border University Students: A Case Study In Saudi Arabia Related To Vision 2030 - Ajlouni, Dr. Mahmoud Mohammad Al (The journal of contemporary issues in business and government, 2021)
The main purpose of this study is to examine the effect of the training level program on environmental awareness of students with different socioeconomic statuses in Northern Border University in the Kingdom of Saudi Arabia, in relation to Vision 2030. Efforts to expand the depth and scope of environmental training level programs that help students in the university to connect with nature often depend on the preparation and development of skilled environmental training. However, the effect of professional development on aspiring environmental training teachers has not been adequately explored.